The influence of the physical properties of aggregates on the ultrasound pulse technique in predicting the compressive strength of concrete - Solís Carcaño, Rómel; Baeza Pereyra, Julio (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The ultrasound pulse technique has been used for more than 50 years, for measuring the quality of concrete elements. Among other applications, the technique has been used for predicting the compressive strength of concrete. This work presents regression models between the ultrasound pulse velocity, and the compressive strength of concrete cylinders, obtained from destructive testing. The results of this research point out that the sole use of the ultrasound technique can predict around 70% of the variability of the compressive strength in the case where the aggregates come from the same region of Mexico.